RENATA ŠERELYTĖ AND SIGITAS PARULSKIS. TWO CASES OF INVOLVING THE POSTCOLONIAL DISCOURSE INTO THE LITHUANIAN PROSE AFTER 1991 - Kowerko-Urbańczyk, Marta (Porównania, 2014)
The text refers to disputes regarding postcolonial studies in the Baltic States. I am deeply interested in Lithuanian literature after 1991, where I observe the relationship between the postcolonial situation and the apparent breakthrough which we can be easily noticed in gender fields. In the novels of Renata Šerelytė and Sigitas Parulskis the reality after the fall of the Soviet Union appears to be a space of humiliation, powerlessness and oppression, from which the subalterns cannot escape. The characters of these novels treated diversity as a threat to their personal identities and decided to search for those who are weaker than themselves to regain the subjectivity taken away from them by the Soviet system. This behaviour results in incoherent worlds created by the Lithuanian writers who struggle with the postcolonial schizophrenia. On the one hand, they try to refer to western paragons. On the other hand, they struggle with the consequences of the postcolonial trauma.